Between Humans And Religious Values (Collaboration In AI-Based Islamic Religious Education Learning) - Sari, Nabila Intan Permata; Thohir, Muhammad; Al Fath, M. Gian Fithoni (el-Tarbawi, 2025)
This study is motivated by the rapid advancement of digital technologies, particularly Artificial Intelligence (AI), which has become a central topic in contemporary educational development. This research aims to examine the role of AI in post-pandemic Islamic Religious Education (Pendidikan Agama Islam/PAI) by assessing students’ satisfaction with AI-assisted learning. The PIECES framework—encompassing Performance, Information and Data, Economics, Control and Security, Efficiency, and Service—was employed to evaluate six key dimensions of system use. A total of 61 PAI students participated in this study through a Likert-scale questionnaire. The findings show that students generally express satisfied perceptions toward the implementation of AI in PAI learning, with most domains falling within the satisfied category and the Performance domain showing a neutral response. These results indicate that AI contributes to improving access to learning resources, supporting learning autonomy, enhancing efficiency, and facilitating more interactive learning experiences. Furthermore, the integration of AI was perceived to remain compatible with ethical and spiritual values in Islamic education when applied responsibly. The novelty of this study lies in its application of the PIECES framework within the context of Islamic Religious Education, providing an empirical model for evaluating the acceptance and effectiveness of AI-assisted learning in post-pandemic higher education. This research offers theoretical and practical insights into how AI can be responsibly integrated into religious education to strengthen learning quality, digital adaptability, and student engagement.